Whole-exome sequencing of polycythemia vera revealed novel driver genes and somatic mutation shared by T-cells and granulocytes - Wang, Linghua (Leukemia, 2014)
To better understand the underlying molecular basis of polycythemia vera (PV), we performed whole-exome sequencing and DNA copy-number analysis of 31 JAK2(V617F)-positive patients and further investigated the evolution of somatic mutations using longitudinal samples. In addition to JAK2(V617F) and 9pUPD, we identified frequent recurrent somatic mutation in ASXL1, TET2, DNMT3A, SF3B1 and NF1. Forty two percent of patients had a somatic mutation in at least one epigenetic modifier gene. In 4 of 31 patients, variant allele abundance suggested mutation of JAK2(V617F) was preceded by other somatic mutations including ASXL1, DNMT3A and SF3B1. Strikingly, in 7 patients, apparent germline variants were detected at COSMIC codons in one or more PV-related genes in which we had also discovered somatic mutations across the cohort, suggesting that some pre-JAK2(V617F) mutations contribute to substantial T-lymphocyte progeny. This study contributes to novel understanding of the complexity of PV pathogenesis.